Investigation of coseismic liquefaction‐induced ground deformation associated with the 2019 Mw 5.8 Mirpur, Pakistan, earthquake using near‐surface electrical resistivity tomography and geological data. Issue 2 (6th March 2021) - Khan, Muhammad Younis; Turab, Syed Ali; Riaz, Muhammad Shahid; Atekwana, Estella A.; Muhammad, Said; Butt, Nabeel Afzal; Abbas, Syed Mohsin; Zafar, Waqar Ali; Ohenhen, Leonard O.
ABSTRACT: An electrical resistivity tomography survey was conducted to assess the subsurface conditions associated with the coseismic liquefaction phenomenon in the epicentral region following the Mw 5.8 Mirpur earthquake (Pakistan) on 24 September 2019. The Mirpur earthquake produced extensive coseismic liquefaction‐induced surface deformations, including: sand blows, ground failure and lateral spreading along the Upper Jhelum Canal and in the nearby villages. Electrical resistivity data were acquired along three profiles and calibrated with available borehole data. The inverted electrical resistivity tomography profiles reveal three regional geoelectric layers, which consist of an upper 2–‐5‐m‐thick discontinuous zones of medium resistivity values ranging from 25 Ωm to 60 Ωm, underlain by a 7–8‐m‐thick zone of low resistivity (<10 Ωm) and a basal layer of high resistivity (> 100 Ωm). Based on geological and geophysical data, we infer that. (1) disrupted geoelectric layers in the shallow subsurface and spatially extended low electrical resistivity (<8 Ωm) layers document the elevated groundwater table due to sudden increase in pore‐water pressure triggered by the Mirpur earthquake. These lenses of high conductivity may represent potential hazards in the case of future earthquakes in the study area. (2) Fracture azimuths vary between 120° ± 15° and 335°–45° (subparallel and orthogonal to the strike of the Himalayan Frontal Thrust. (3) Common coseismic deformational features (e.g., sand blow and ground fracture) are located within the zone of maximum‐recorded ground shaking (intensity of VI) and underlain by Quaternary alluvial sediments. (4) Mega fractures (1.60 m wide and up to 187 m long) oriented parallel to the canal resulted from lateral spreading. We conclude that high resistivity structures extending from depth to the shallow subsurface resulted from either intrusion of air or eruption of sands from layer three. We suggest that high‐resolution geoelectrical imaging is a valuable complementary tool for evaluating the extent of subsurface liquefaction features and in understanding coseismic deformation during earthquakes, which can help with seismic hazard analysis and mitigation in seismically active regions.